Education on Forming Anti-Narcotics Peer Groups for Realizing Drug-Free Villages in Langkat Regency - Syahferi Anwar; Balqis Nurmauli Damanik; Khairunnisa Situmorang; Humaida Hanim; Henny Purwanti; Linawati Togatorop (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The issue of drug abuse among Indonesian teenagers has reached alarming levels in 2024, with a national prevalence of 2.4% and 2.9% in North Sumatra Province. In Langkat Regency, there has been a 15% increase in drug cases among teenagers compared to the previous year. To address this challenge, the Desa Bersinar (Drug-Free Village) program was launched in Langkat Regency, utilizing an innovative peer group method in anti-drug interactive dialogues. This method was chosen for its effectiveness in fostering personal and relevant communication among teenagers, allowing anti-drug messages to be conveyed more deeply. The implementation involved collaboration between BNNK Langkat, Universitas Haji Sumatera Utara, and STIKes Columbia Asia Medan, integrating the program into community service initiatives. Discussions facilitated by peer leaders, supported by academics, used the SIGAB BNN Module as a comprehensive guide, aiming to create a drug-free school environment and develop a generation more aware of the dangers of drugs